Adhesion of Salmonella enteritidis to stainless steel surfaces - Oliveira, Kelly (2007)
Adhesion of microorganisms to food processing surfaces and the problems it causes are a matter of strong concern to the food industry. Contaminated food processing surfaces may act as potential sources of transmission of pathogens in food industry, catering and in the domestic environments. Several studies have shown that adhesion of bacteria to surfaces partly depends upon the nature of the inert surfaces and partly upon the bacterial surface properties. The aim of this study was to compare the adhesion of four different strains of Salmonella Enteritidis to stainless steel 304 (SS 304). The effect of surface hydrophobicity and surface elemental composition on the adhesion process was also analysed. Hydrophobicity was evaluated through contact angle measurements using the sessile drop method. All the strains studied showed positive values of the degree of hydrophobicity (ΔGlwl) and so can be considered hydrophilic while stainless steel revealed a hydrophobic character. Bacterial cell surface composition was measured using X-ray photoelectron spectroscopy (XPS). The XPS results corroborated the similarity of the values of the degree of hydrophobicity obtained by contact angles. The different Salmonella strains showed similar elemental composition and cell surface physico-chemical properties. Nevertheless, S. Enteritidis MUSC presented higher adhesion ability to SS 304 (p<0.05). It can be concluded that the physico-chemical properties of the strain does not explain the ability of adhesion to stainless steel. Other factors like the production of polysaccharides must be considered.